Higher Caloric Refeeding Is Safe in Hospitalised Adolescent Patients with Restrictive Eating Disorders. (12th May 2016) - Parker, Elizabeth K.; Faruquie, Sahrish S.; Anderson, Gail; Gomes, Linette; Kennedy, Andrew; Wearne, Christine M.; Kohn, Michael R.; Clarke, Simon D.
Abstract : Introduction . This study examines weight gain and assesses complications associated with refeeding hospitalised adolescents with restrictive eating disorders (EDs) prescribed initial calories above current recommendations. Methods . Patients admitted to an adolescent ED structured "rapid refeeding" program for >48 hours and receiving ≥2400 kcal/day were included in a 3-year retrospective chart review. Results . The mean (SD) age of the 162 adolescents was 16.7 years (0.9), admission % median BMI was 80.1% (10.2), and discharge % median BMI was 93.1% (7.0). The mean (SD) starting caloric intake was 2611.7 kcal/day (261.5) equating to 58.4 kcal/kg (10.2). Most patients (92.6%) were treated with nasogastric tube feeding. The mean (SD) length of stay was 3.6 weeks (1.9), and average weekly weight gain was 2.1 kg (0.8). No patients developed cardiac signs of RFS or delirium; complications included 4% peripheral oedema, 1% hypophosphatemia (<0.75 mmol/L), 7% hypomagnesaemia (<0.70 mmol/L), and 2% hypokalaemia (<3.2 mmol/L). Caloric prescription on admission was associated with developing oedema (95% CI 1.001 to 1.047;p = 0.039 ). No statistical significance was found between electrolytes and calories provided during refeeding. Conclusion . A rapid refeeding protocol with the inclusion of phosphate supplementation can safely achieve rapid weight restoration without increased complications associated with refeeding syndrome.